2010
DOI: 10.1002/ccd.22395
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transcatheter arterial embolization of inferior pancreatico‐duodenal artery aneurysms associated with celiac artery stenosis or occlusion

Abstract: IPDA aneurysms associated with celiac axis stenosis can be successfully treated with percutaneous embolization with minimal recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Nowadays, endovascular treatment becomes the first‐line method of treating almost all visceral aneurysm with high success rates, and low morbidity and mortality . Several techniques with various embolic agents, for endovascular treatment of visceral artery aneurysms and pseudoaneurysms, have been reported in literature . We report a case of saccular aneurysm of the third JA treated with endovascular embolization using the Amplatzer Vascular Plug 4 (AVP 4) (St. Jude Medical, St. Paul, MN) with the isolation technique.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, endovascular treatment becomes the first‐line method of treating almost all visceral aneurysm with high success rates, and low morbidity and mortality . Several techniques with various embolic agents, for endovascular treatment of visceral artery aneurysms and pseudoaneurysms, have been reported in literature . We report a case of saccular aneurysm of the third JA treated with endovascular embolization using the Amplatzer Vascular Plug 4 (AVP 4) (St. Jude Medical, St. Paul, MN) with the isolation technique.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these patients are treated with coil embolization when symptomatic. [6][7][8] Association of SMA stenosis with pancreaticoduodenal artery and GDA aneurysm is rare. [9][10][11][12][13] Moore et al reported that the association of pancreaticoduodenal artery aneurysms is more common with celiac axis stenosis than SMA stenosis compared with GDA aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Methods for follow-up imaging after endovascular treatment of vis- (6,7,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). In regards to the follow-up imaging modality, CT examination was reported in 13 publications and was thus the most widely used (7,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). In fact, CT was the only follow-up examination method used in nine of these publications (13,14,16,(19)(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…In regards to the follow-up imaging modality, CT examination was reported in 13 publications and was thus the most widely used (7,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). In fact, CT was the only follow-up examination method used in nine of these publications (13,14,16,(19)(20)(21)(22)(23)(24). Follow-up outcomes of completely thrombosed aneurysms were reported in 11 publications (6, 13-16, 18-20, 22-24), 10 of which were evaluated by CT (13-16, 18-20, 22-24).…”
Section: Discussionmentioning
confidence: 99%